Sinergi Perguruan Tinggi, Industri, UMKM, dan Masyarakat dalam Pemanfaatan Limbah Aspal dan Limbah Karung Pupuk untuk Perbaikan Jalan Desa di Kabupaten Aceh Besar - Machdar, Izarul; Ali, Masri; Hajni, Nurul (Universitas Syiah Kuala, 2025)
This community engagement initiative was designed to repurpose plastic waste from used fertilizer sacks and reclaimed asphalt pavement as composite materials for repairing rural roads in Gampong Blang Krueng, Baitussalam Subdistrict, and Gampong Lamteuba Droe, Seulimuem Subdistrict, Aceh Besar Regency. The program addressed two major challenges: the growing accumulation of plastic waste that harms the environment and the deteriorating condition of local roads due to aging and frequent heavy rainfall. The activity was carried out through several key stages, including problem identification, community consultation, preparation of tools and materials, on-site implementation, and post-activity evaluation. The plastic waste obtained from fertilizer sacks was cleaned, shredded into small fragments, and then blended with hot asphalt and reclaimed asphalt pavement at around 160C before being laid and compacted on the road surface. Findings from the implementation revealed that the plasticasphalt blend produced a stronger, smoother, and more resilient road surface capable of withstanding tropical weather conditions and light vehicular traffic. Beyond the technical outcomes, the initiative also fostered greater community awareness of sustainable plastic waste management and enhanced collaboration among universities, industries, small and medium enterprises, and local residents in promoting the use of environmentally friendly technologies for infrastructure improve-ment.